2023
DOI: 10.1111/1753-0407.13387
|View full text |Cite
|
Sign up to set email alerts
|

The association between daytime napping and risk of type 2 diabetes is modulated by inflammation and adiposity: Evidence from 435 342 UK‐Biobank participants

Abstract: Background: Existing evidence concerning the relationship between daytime napping and type 2 diabetes (T2D) is inconsistent, and whether the effects of napping differ by body fat percentage (BFP) and C-reactive protein (CRP) is unclear. We aimed to investigate the association between daytime napping frequency and T2D risk and whether such an association was modified by BFP and CRP. Methods: We included 435 342 participants free of diabetes from the UK Biobank. Participants were categorized as nonnappers, occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…McWhorter et al 32 investigated the relationship between napping frequency and T2DM using napping less than three times a week as a control and found that frequent napping (≥3 times/week) was associated with a higher risk of T2DM. Zhou et al 46 conducted a survey of 435 342 adults aged 40–69 years and found that higher nap frequency was associated with an increased T2DM risk. Data from the remaining 28 studies could be pooled, and the results were as follows.…”
Section: Resultsmentioning
confidence: 99%
“…McWhorter et al 32 investigated the relationship between napping frequency and T2DM using napping less than three times a week as a control and found that frequent napping (≥3 times/week) was associated with a higher risk of T2DM. Zhou et al 46 conducted a survey of 435 342 adults aged 40–69 years and found that higher nap frequency was associated with an increased T2DM risk. Data from the remaining 28 studies could be pooled, and the results were as follows.…”
Section: Resultsmentioning
confidence: 99%
“…One study conducted in pregnant women (aged 23 years) found that napping frequency did not have a significant association with 1-h OGTT values or hyperglycemia (N=63) ( 47 ). High napping frequency was found associated with an increased risk of developing T2D (N=435,342) (aged 56 years, 55% females) ( 48 ). Compared with non-nappers, people with regular napping were 1.3 times more likely to have poor glycemic control (N=12,997) (aged 59 years, 38% females) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%